2022
DOI: 10.1111/jppi.12415
|View full text |Cite
|
Sign up to set email alerts
|

Key learnings from COVID‐19 to sustain quality of life for families of individuals with IDD

Abstract: COVID‐19 has very publicly had profound impacts on the health system of every country in the world. Over 4.5 million people have lost their lives. School closures worldwide where up to 1.6 billion of the world’s children have been out of school, are also prominent in world news. Behind these public impacts are the families. In this paper, we focus on the experiences of families with people with intellectual and developmental disabilities (IDD) through analysis of two data sets: the emerging research literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Furthermore, while recent research has generally highlighted the negative impacts of the COVID‐19 pandemic on autistic individuals, the literature overall highlights contrasting evidence around the effects of the pandemic on family caregivers and their interactions with children (Bailey et al, 2021 ; Fontanesi et al, 2020 ; Greenway & Eaton‐Thomas, 2020 ; Mumbardó‐Adam et al, 2021 ; Narzisi, 2020 ; Navas et al, 2022 ; O'Connor Bones et al, 2022 ; Tsibidaki, 2021 ; Wanjagua et al, 2022 ). The evidence finds that parents of autistic children were very stressed and struggled during the early phase of the pandemic (Amorim et al, 2020 ; Asbury et al, 2021 ; Pellicano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while recent research has generally highlighted the negative impacts of the COVID‐19 pandemic on autistic individuals, the literature overall highlights contrasting evidence around the effects of the pandemic on family caregivers and their interactions with children (Bailey et al, 2021 ; Fontanesi et al, 2020 ; Greenway & Eaton‐Thomas, 2020 ; Mumbardó‐Adam et al, 2021 ; Narzisi, 2020 ; Navas et al, 2022 ; O'Connor Bones et al, 2022 ; Tsibidaki, 2021 ; Wanjagua et al, 2022 ). The evidence finds that parents of autistic children were very stressed and struggled during the early phase of the pandemic (Amorim et al, 2020 ; Asbury et al, 2021 ; Pellicano et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on cross sectional designs collected during early months of COVID‐19 reported that families with autistic children registered greater behavioral problems and parental distress compared with families of nonautistic children during the COVID‐19 restrictions (Levante et al, 2021 ). However, the overall evidence regarding the impact of the pandemic on outcomes in families with autistic children or children with IDs remains inconclusive (Bailey et al, 2021 ; Fontanesi et al, 2020 ; Greenway & Eaton‐Thomas, 2020 ; Mumbardó‐Adam et al, 2021 ; Narzisi, 2020 ; Navas et al, 2022 ; O'Connor Bones et al, 2022 ; Pellicano et al, 2021 ; Tsibidaki, 2021 ; Wanjagua et al, 2022 ). One explanation is that much of the research into the impact of the pandemic on parental outcomes is subject to methodological challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The self-reports of children with SEN and disabilities on remote learning would broaden and deepen the perspective on how their individual educational and socio-emotional needs were addressed, and it would provide insight on engagement in remote learning opportunities and supports from school services and other professionals, such as therapists. Whatever the focus, preparedness for future crisis situations should certainly emerge from the documented lived experiences of parents in this and other published studies (e.g., Chen et al, 2020;Dhiman et al, 2020;Wanjagua et al, 2022).…”
Section: Slovenian Parentsmentioning
confidence: 80%
“…For families of children with SEN and disabilities, the COVID‐19 pandemic and its accompanying school closures quite suddenly thrust them into a new and important role in their children's education (Akdal et al, 2021). Asbury et al (2021) noted that these families usually experienced more stressors than families with neurotypical children, and Nadler et al (2021) pointed out that their new role added numerous stresses for the family, including disruptions to established daily routines and financial burden (see also Chen et al, 2020; Dhiman et al, 2020; Fontanesi et al, 2020; Wanjagua et al, 2022). A study conducted in England showed the importance of providing support to parents when setting up the routines for transitioning from personal/direct teaching in classrooms to remote teaching, and the opposite transition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have studied how the COVID-19 pandemic impacted on people with intellectual and developmental disabilities. Results found a clear impact of the missing routine health checks and isolation, making the COVID-19 pandemic a potential source of stress and trauma for the disability community (Lund et al, 2020;Wanjagua et al, 2022).…”
mentioning
confidence: 99%